(untitled) (Diametros, 2010)
Polish legislation provides for the issuance of codes of ethics by local governments for professions of public trust, especially the legal and medical professions. There are diverse views as to the legal nature of such codes: a one-tier position (the codes issued under the authority of the legislation are part of the legal system), a two-tier position (the parallelism of professional conduct and ethical standards), or a compromise position in which ethical codes are recognized as acts of "soft law". The peculiarity of the 2002 Civil Service Code of Ethics is that it concerns an important part of public service (not the professions of public trust), that it was established by the Prime Minister (not by way of professional self-regulation) and that, starting from more general principles of public service, it was constructed by deriving professional rules of conduct from the constitutional principles of service: integrity, professionalism, impartiality and political neutrality. The current Civil Service Act of 2008 includes the legal basis for the codification of the ethics of the civil service corps by the Prime Minister. Past experience indicates that the new code should be an adaptation of the 2002 Code.